2016
DOI: 10.18632/oncotarget.8293
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive repertoire of tRNA-derived fragments in prostate cancer

Abstract: Prostate cancer (PCa) is the most common cancer among men in developed countries. Although its genetic background is thoroughly investigated, rather little is known about the role of small non-coding RNAs (sncRNA) in this disease. tRNA-derived fragments (tRFs) represent a new class of sncRNAs, which are present in a broad range of species and have been reported to play a role in several cellular processes. Here, we analyzed the expression of tRFs in fresh frozen patient samples derived from normal adjacent pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
196
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(202 citation statements)
references
References 42 publications
6
196
0
Order By: Relevance
“…Since each tRNA family may be composed of several isotypes (anticodons) and individual sequences (different tRNA sequences for each anticodon), this appears to be non-random differential cleavage, as has been shown previously. 27,29,31,32 Group C had significantly more tDRs for Val (adjusted p = 0.01) and Gly (adjusted p = 0.017). In addition, there was a proportionately higher fraction of reads aligned to positions 46-72 in Groups A and B than in Group C, with greater representation of phenylalanine-encoding tDRs in Group B (adjusted p = 9.3E-05 for C versus B).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Since each tRNA family may be composed of several isotypes (anticodons) and individual sequences (different tRNA sequences for each anticodon), this appears to be non-random differential cleavage, as has been shown previously. 27,29,31,32 Group C had significantly more tDRs for Val (adjusted p = 0.01) and Gly (adjusted p = 0.017). In addition, there was a proportionately higher fraction of reads aligned to positions 46-72 in Groups A and B than in Group C, with greater representation of phenylalanine-encoding tDRs in Group B (adjusted p = 9.3E-05 for C versus B).…”
Section: Resultsmentioning
confidence: 95%
“…There are two discrete populations of tDRs, one of 33 nucleotide 5’ tDHs that encompasses the D loop with terminal cleavage before the anticodon. 31 The second group is composed of residues 46-72, encompassing the variable loop and the T loop of the full tRNA, similar to the type V set of tRFs that have been previously identified, 32 and may represent truncated 3’ tRHs. In general, only certain tRNA families (coding for the same amino acid) are represented in each group.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Unbiased deep sequencing of human sncRNAs has shown the changes of tRFs in response to various types of diseases, including cancer, neuro-developmental disorders and infections; however, the significance of tRFs in diseases and the associated molecular mechanisms remain largely unknown, mainly due to the lack of methods for the functional studies [9,10,[19][20][21]. Following our report on the function of tRF5-GluCTC in regulating RSV replication [10,[22][23][24], many recent studies suggest the role of tRFs in infectious diseases; however, other important tRFs in infectious diseases have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, tRNA halves can prevent apoptosis of cancer cells by binding to cytochrome C or promote the assembly of stress granules that help cells survive in adverse conditions [30]. Another recent study indicated that two specific tRFs derived from tRNA Lys-CTT and tRNA Phe-GAA were good indicators of progression-free survival (PFS) and candidate prognostic markers [31]. Taken together, these findings strongly suggest a functional role for tRNA-derived fragments in cancer progression.…”
Section: Introductionmentioning
confidence: 99%